Long-term prognostic value of left ventricular dyssynchrony assessment by phase analysis from myocardial perfusion imaging. Issue 1 (20th October 2010) - Pazhenkottil, Aju P; Buechel, Ronny R; Husmann, Lars; Nkoulou, René N; Wolfrum, Mathias; Ghadri, Jelena-Rima; Kummer, Janine; Herzog, Bernhard A; Kaufmann, Philipp A
Abstract : Objective: To assess the value of left ventricular (LV) dyssynchrony, using phase analysis of nuclear single-photon emission computed tomography (SPECT) myocardial perfusion imaging (MPI) as independent predictor of cardiac events. Methods: Phase analysis using Emory Cardiac Toolbox was applied on gated rest MPI scans to assess LV dyssynchrony in a total of 202 patients. Follow-up was obtained in 197 patients (97.5%). Major adverse cardiac events (MACE) (cardiac death and hospitalisation for any cardiac reasons, including worsening of heart failure, non-fatal myocardial infarction, unstable angina and coronary revascularisation) were determined using the Kaplan–Meier method. Cox proportional hazard regression was used to identify independent predictors of cardiac events. Results: At a median follow-up of 3.2±1.2 years, 41 patients had at least one event, including 5 cardiac deaths. LV dyssynchrony (n=35) was associated with a significantly higher incidence of MACE (p<0.001) and proved to be an independent predictor of cardiac events. Conclusion: LV dyssynchrony assessed by phase analysis of gated SPECT-MPI is a strong predictor of MACE independent of other known predictors such as perfusion defects or decreased LV ejection fraction.